Assessment of the groundwater quality and pollution in Kabul City, Afghanistan - Zahid, Safiullah; Asmawi, M. Zainora; Abdullah, Muhammad Faris (RMP PUBLICATIONS, 2019)
Kabul, the Capital of Afghanistan is counting as one of the rapidly growing cities in Asia, one-third of its population have access to the water supply network. In addition to that, the public sanitation system does not exist in the city, which leads to contamination of the groundwater in the city. However, the purpose of this study is to assess the groundwater quality and to analyze the main sources of water pollution in Kabul city. In this relation, more than 450 samples of groundwater which covers the samples from residential houses, water supply wells and public water supply system reservoirs, have been collected and analyzed for physical and biological characteristics, which reveal the existence of Total Coliform bacteria by 12.9% and Fecal Coliform bacteria by 9.6% in the groundwater of the Kabul city. Furthermore, 49 water supply wells were also investigated to find the main sources of water pollution in the city and the result discovered that 13 different sources exist that may affect the groundwater quality of the city to its greater extent.